The Mediating Role of Self-Efficacy and Social Support in the Effect of Psychological Hardiness on the Quality of Life of Physically Disabled People - Akbari, Mahdi (Psychological Research in Individuals with Exceptional Needs, 2026)
The present study aimed to investigate the structural relationship between psychological hardiness and quality of life in physically and motor disabled individuals, with the mediating roles of self-efficacy and perceived social support. This applied, cross-sectional, correlational study was conducted using structural equation modeling among physically and motor disabled individuals in Mazandaran Province, Iran. The statistical population consisted of approximately 26,000 individuals registered in the provincial Welfare Organization, from whom 424 participants aged 14–40 years (277 males and 147 females) were selected through two-stage cluster sampling from Sari, Amol, Behshahr, and Chalus cities. Data were collected using the Ahvaz Psychological Hardiness Questionnaire, the SF-36 Quality of Life Questionnaire, Sherer’s Self-Efficacy Scale, and the Sherbourne and Stewart Social Support Scale. The instruments demonstrated acceptable reliability coefficients ranging from 0.86 to 0.91. Descriptive statistics, Pearson correlation coefficients, Sobel tests, and structural equation modeling were performed using SPSS-22, AMOS, and SmartPLS software at a 95% confidence level. The results demonstrated significant positive relationships among all study variables. Psychological hardiness had significant direct effects on self-efficacy (β=0.10, T=2.09, P<0.01), perceived social support (β=0.27, T=2.53, P<0.01), and quality of life (β=0.10, T=2.94, P<0.01). Self-efficacy also showed a significant direct effect on quality of life (β=0.11, T=2.55, P<0.01), while perceived social support significantly predicted quality of life (β=0.18, T=2.71, P<0.01). Pearson correlation analysis revealed the strongest correlation between psychological hardiness and quality of life (r=0.853, P<0.01). Sobel test findings confirmed the mediating role of self-efficacy (β=0.04, Z=2.57, P=0.01) and perceived social support (β=0.03, Z=2.74, P=0.001) in the relationship between psychological hardiness and quality of life. The proposed model explained 18% of the variance in self-efficacy, 14% in social support, and 11% in quality of life. The findings indicate that psychological hardiness contributes significantly to improving the quality of life of physically disabled individuals both directly and indirectly through enhancing self-efficacy and perceived social support. Strengthening resilience-related psychological characteristics, promoting self-efficacy beliefs, and expanding supportive social networks may improve mental health and overall life satisfaction among individuals with physical and motor disabilities. Therefore, psychological interventions and rehabilitation programs focused on resilience enhancement and social support development are recommended for improving the well-being and quality of life of this population.